The Implementation of Aqidah in the Qur'an on the Behavior of MA Raudlatul Huda Al-Islamy Students - Zahro, Nayyirotul Anzumi; Jannah, Siti Roudhotul (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to examine the implementation of the aqidah in the Al-Qur'an on student behavior at MA Raudlatul Huda Al-Islamy. Aqidah has a central role in shaping students' character and morality, which is not only related to human relationships with Allah SWT, but also relationships between humans and the environment. Along with the times and external influences such as technology and social media, implementing aqidah in student behavior has become a challenge in itself. This research uses a qualitative approach with descriptive methods to explore this phenomenon in depth through observations, interviews with Aqidah Akhlak teachers, madrasa heads, and students. The research results show that although the majority of students have demonstrated behavior that reflects the values of aqidah, awareness of these values still varies. The influence of the external environment, especially social media, is one of the main obstacles in the internalization of aqidah. Collaboration between schools, parents and the community has proven important in strengthening the implementation of aqeedah in student behavior. This research concludes that with the right approach and support from all parties, the implementation of aqidah can produce good character and behavior that reflects Islamic values.